Assessment of effective doses for fluoroscopy-guided balloon dilatation of benign esophageal strictures in pediatric medicine - Yu. N. Kapyrina; A. V. Vodovatov; V. G. Puzyrev; M. I. Komissarov; I. Yu. Aleshin; V. Yu. Golikov; V. I. Orel (Радиационная гигиена)
Interventional examinations are associated with high levels of patient exposure per examination, which makes it particularly important to monitor individual patient doses and to assess radiation risks. The aim of this study was the assessment of effective doses for fluoroscopy-guided balloon dilatation of benign esophageal strictures, whichwasperformedonpediatricpatientsaged 1 to 2 yearsatthe Departmentof Radiosurgical Methodsof Diagnosis and Treatment of St. Petersburg State Pediatric Medical University. Patient exposure patterns were basedonourowndatacollection.    Thecalculationofeffectiveandorgandosesofpatientsnormalizedbythevalue of the dose area product measured during the study was carried out using PCXMC 2.0 software. The conversion coefficients from the dose area product to the effective dose were calculated using tissue weighting coefficients from the ICRP Publications 60 and 103 their values were 10.7 and 11.7 µSv/cGy cm2, respectively. The results of verification of the method indicated that the use of inappropriate conversion coefficients leads to an almost double underestimation of children’s effective doses. Differences in the values of conversion coefficients are significant and are explained by differences in voltage, source to image distance, and irradiation field size. A simplified model of patient exposure was proposed, which is described by a single irradiation field. The assessment of effective doses using multi-field and single-field irradiation model shows comparable results, which allows using the differentiated approach to the assessment of radiation doses of patients.